Role of Land Professionals and Spatial Data Infrastructure in Disaster Risk Reduction: In the Context of Post 2015 Nepal Earthquake - Bhatta, Ganesh Prasad; Dangol, Susheel; Sapkota, Ram Kumar (Journal on Geoinformatics, Nepal, 2016)
N/A